2020
DOI: 10.1002/pam.22259
|View full text |Cite
|
Sign up to set email alerts
|

Welcome Mats and On‐Ramps for Older Adults: The Impact of the Affordable Care Act's Medicaid Expansions on Dual Enrollment in Medicare and Medicaid

Abstract: For many low‐income Medicare beneficiaries, Medicaid provides important supplemental insurance that covers out‐of‐pocket costs and additional benefits. We examine whether Medicaid participation by low‐income adults age 65 and up increased as a result of Medicaid expansions to working‐age adults under the Affordable Care Act (ACA). Previous literature documents so‐called “welcome mat” effects in other populations but has not explicitly studied older persons dually eligible for Medicare and Medicaid. We extend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…Examining expansions of Medicaid and the State Children's Health Insurance Program to parents in the late 1990s and early 2000s along with changes in employer-provided insurance availability, Glied and Hong (2018) find insurance coverage expansions led to lower Medicare spending per beneficiary. This was a similar finding to that of McInerney, Mellor, and Sabik (2017), who study individual-state Medicaid expansions pre-dating the ACA. Both studies, however, present suggestive evidence that the spending crowded out in these cases was low-value care.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Examining expansions of Medicaid and the State Children's Health Insurance Program to parents in the late 1990s and early 2000s along with changes in employer-provided insurance availability, Glied and Hong (2018) find insurance coverage expansions led to lower Medicare spending per beneficiary. This was a similar finding to that of McInerney, Mellor, and Sabik (2017), who study individual-state Medicaid expansions pre-dating the ACA. Both studies, however, present suggestive evidence that the spending crowded out in these cases was low-value care.…”
Section: Introductionsupporting
confidence: 83%
“…Thus, post-65 beneficiaries could only be affected by the supply-side and downward-sloping-demand effects, while the pre-65 individuals could be influenced by both in addition to intertemporal substitution. Moreover, separating the cohorts this way also allows us to examine changes in Medicaid coverage separately and provide further understanding of the results of McInerney, Mellor, and Sabik (2021), which showed sizable spillovers in coverage (on-ramp effects) for pre-65 beneficiaries, but did not provide separate estimates for post-65 enrollees.…”
Section: Introductionmentioning
confidence: 99%
“…The two exceptions for the elderly sample include exercise, for which I find a 1.1 percentage point increase ( p < 0.05) and mammogram, for which I find a 1.9 percentage point decrease ( p < 0.01). Recent work has shown that though the ACA Medicaid expansions targeted working‐age adults, they also had some spillover effects on elderly adults dually eligible for Medicare and Medicaid (McInerney, Mellor, & Sabik, 2018). Small increase in insurance coverage may help explain the increase in exercise among elderly adults.…”
Section: Resultsmentioning
confidence: 99%
“…Spillovers may arise from the so-called welcome mat phenomenon, in which, for example, increased publicity about Medicaid and a streamlined application process attract people who were eligible under traditional criteria but who had not enrolled previously and then underwent the eligibility process. 13,14 Other structural changes to the Medicaid program after ACA expansion that targeted potential eligible adults might also have been associated with increased coverage and with increased demand for LTC. For example, the increase in case management as a part of contracts for accountable care organizations could make case managers more aware of Medicaid application processes.…”
Section: Introductionmentioning
confidence: 99%